2014
DOI: 10.3906/sag-1209-102
|View full text |Cite
|
Sign up to set email alerts
|

Acute Q fever among febrile patients in Zahedan, southeastern Iran

Abstract: It is shown that the electroweak physics of the electron and the muon is based on the left-right gauge model with the mixing parameters 0.2254 and 0.2746. These mixing parameters are determined by the masses of the electron and the muon. The electroweak physics of the Tau-lepton and its left-handed neutrino is based on the gauge group SU(2)LXU(1).The mixing parameter for this gauge model is 0.5 and is determined by the mass of the charged Tau-lepton. The W and Z bosons that mediate the electroweak physics of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…In this study, 32% of participants showed evidence of previous infection (past infection) to Q fever; this rate was less than one in Zahedan city (34.3%) [26] and Kerman Province (36%) [18]. In similar studies, 35.5% in Mali [29], 21.74% in Croatia [30] and 8.7% [27] in Denmark were previously infected with Q fever.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…In this study, 32% of participants showed evidence of previous infection (past infection) to Q fever; this rate was less than one in Zahedan city (34.3%) [26] and Kerman Province (36%) [18]. In similar studies, 35.5% in Mali [29], 21.74% in Croatia [30] and 8.7% [27] in Denmark were previously infected with Q fever.…”
Section: Discussionmentioning
confidence: 46%
“…It was also shown that 32% of the participants had serological evidence of previous infection (past infection) to Q fever. In a similar study in Zahedan city (southeastern Iran) in 2011, 35.2% of 105 suspected feverish patients were diagnosed acute Q fever [26], which is much higher than the current report. Furthermore, in another study conducted among febrile patients suspected to have brucellosis in Kerman Province (southern Iran), 36% had phase II IgG antibody of Q fever [18].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In 2011, Metanat et al (12) designed a study in Zahedan in which 105 febrile patients with a probable diagnosis of brucellosis were investigated using the IFA technique for detecting C. burnetii antibodies in sera. The results showed that 35.2% of the patients had positive sera on the acute form of the fever and most people lived in rural areas.…”
Section: Discussionmentioning
confidence: 99%